Analysis of Farming Contribution to Economic Growth and Poverty Alleviation in the South African Economy: A Sustainable Development Goal Approach - Mpundu, Mubanga; Bopape , Onkabetse (International Journal of Economics and Financial Issues, 2022)
The agricultural sector is important in South Africa because it contributes approximately 2.53 percent to the country’s Gross Domestic Product. Agriculture can contribute significantly to economic growth, by means of food production and job creation and thereby it can play an important role in reducing poverty. This study examines the impact of farming on economic growth and the possible role it plays in poverty alleviation in South Africa. The United Nation Department of Economic and Social Affairs highlights the first three sustainable development goals in line with poverty alleviation, zero hunger and good health and wellbeing for all. The article analysed the impact of farming on gross domestic product from 2002Q1 – 2021Q4 factoring in part of the period for COVID-19. A quantitative method approach was used with an application of the Vector Error Correction Method to check and analyse the behaviour of variables both in the short run and long run using E-views 12 software. Data was retrieved from the South African Reserve Bank, Statistics SA and Quantec. Results showed that variables where cointegrated meaning there was a long run relationship between the dependent variable GDP and the independent variables comprising of consumer price index, consumption, inflation, and unemployment used as proxies in understanding how farming affects economic growth and ultimately consumer well-being. Furthermore, it was found that without consumption there is no economic growth meaning the consumption of livestock, crops and export or trade between countries leads to growth. Employment is also needed in the farming industry, the availability of labour assists in faster production which leads to economic growth. Employment is also needed in the farming industry, the availability of labour assists in faster production which leads to economic growth. There be data on subsistence agriculture and ongoing collection of reliable statistics to monitor the success of this initiative are also needed.